DIFFERENCES STOCK RETURN BETWEEN COMPANY WHICH HAS HIGH ACCOUNTING CONSERVATISM LEVEL AND LOW ACCOUNTING LEVEL TO COMPANY REGISTERED AT STOCK EXCHANGE OF INDONESIA PERIOD 2010-2014 - Haninun HANINUN; Angrita Denziana; Hepiana Patmarina; Theresia Aprilliani (UBL, 2016)
This research has aims to analyze difference stocks return toward company with high conservatism level and low to company that is registered at Stock Exchange of Indonesia (BEI) period year 2010-2014. Hhypothesis that is submitted is including difference stock return between company with high accounting conservatism level and low. Sample in this research is company LQ45 that is registered at Stock Exchange of Indonesia (BEI) period year 2010-2014. Sampling technique which is used purposive sampling so it is reached amount sample as much as 155 companies. Data that is used in this research including net profit plus depreciation, cash flow from operational activity, and operational closing price, and stock closing price. Analysis technique for examination hypothesis using average difference test (Independent Sample t-Test). Test Result Independent Sample t-Test showed that is not include difference stock return between companywhich has high conservatism level and low.